WeServe : Online Service Marketplace mobile application for UNIMAS - See, Yao Fung (Universiti Malaysia Sarawak (UNIMAS), 2019)
Nowadays, online marketplace become more trendy for people to do transaction. People can buy and sell variety of goods, product, or services via online platform. Like most other people, student of UNIMAS familiar with the usage of these online platforms in order to enquire services such as rent car, request tuition services, and so on. Nevertheless, the efficiency of these online platform cannot satisfy their normal daily usage on the online platform. Students are not able to enquire for various of local services around the campus efficiently through these online platforms. Hence, a mobile applications platform named WeServe is proposed to solve this issues as it provide the features of post and search for services in the form of classifiedadvertisement which are simple and easy to be searched too. Furthermore, students can also get themselves involve into small business too as if they want to. They can become one of the services provider where promoting their business services via this WeServe, Overall, this proposed system aim to ease and benefits UNIMAS students by allowing them to acquire or posting services onto the systems.